MANAJEMEN PENGELOLAAN WAKAF TUNAI DI INDONESIA - Atabik, Ahmad (UIN Sunan Kudus, 2014)
This article describes the cash waqf management in Indonesia. Acash waqf endowments performed person, group of people, and institutionsor legal entities in the form of cash. Endowments cash is still being debatedamong scholars’ whether legitimate or not, and the management of cash waqfprofessionally still a discourse and not many people or institutions that canaccept such endowments models. This article also discusses the definition, thelegal basis and the cash endowments history. Also discussed about cash waqfas the foundation of economic development of society by opening the rigidityof Muslims against this cash waqf, also economic prospects waqf property;how the institution of waqf in Islamic countries has been successful both interms of the welfare society places of worship, social, educational, health andother essential infrastructure. Endowments cash in reality also has to serveas economic empowerment; waqf potential as one of the instruments for theeconomic empowerment of Muslims although management in Indonesia is stillnot good. Yet judging by the numbers, waqf property in Indonesia is quitelarge. Most of the endowment in the form or used for houses of worship, Islamiceducational institutions, public cemetery and others who averaged in the formof endowments is not productive. Therefore, the existence of endowments inIndonesia today need special attention, because the existing endowment for agenerally still shaped objects that do not move that basically have considerablepotential as productive lands are located to be managed productively.